The Influence of Playgrounds on Early Childhood Social Skills - Wahyuningtyas, Dessy Putri; Ahmad, Nafilah Salim (UNIVERSITAS PAKUAN, 2023)
Social skills are skills that help children to develop their knowledge of themselves, to recognize the diverse behavior of others and the circumstances around them. However, many parents ignore this and focus on the other child’s abilities. The aim of this study is to find out whether the children's playground or playground in the Malang town square already meets the criteria for being eligible or child-friendly, to know the opinions of parents about the playground available in Malang Town square on the social abilities of the child, and the influence of the presence of a child's playing park on the child’s social capacities. The study used a quantitative approach with the survey method for visitors who came to the children’s playground in Malang town square with a total of 90 respondents parents or accompanying children aged 4 – 5 years and 5 – 6 years. The data collection technique in this study uses a closed questionnaire. For the testing of the hypothesis, the study used the One Sample T-Test and a simple linear regression test using SPSS software. The findings obtained show that there is an influence of children’s playgrounds in the Malang Town Square on the social abilities of children.